Deep brain stimulation of the nucleus accumbens in treatment-resistant alcohol use disorder: a double-blind randomized controlled multi-center trial - Bach, Patrick; Luderer, Mathias; Müller, Ulf Joachim; Jakobs, Martin; Baldermann, Juan Carlos; Voges, Jürgen; Kiening, Karl; Lux, Anke; Visser-Vandewalle, Veerle; Bogerts, Bernhard; Kuhn, Jens; Mann, Karl (Translational Psychiatry, 2023)
Treatment resistance in alcohol use disorders (AUD) is a major problem for affected individuals and for society. In the search of new treatment options, few case studies using deep brain stimulation (DBS) of the nucleus accumbens have indicated positive effects in AUD. Here we report a double-blind randomized controlled trial comparing active DBS (“DBS-EARLY ON”) against sham stimulation (“DBS-LATE ON”) over 6 months in n = 12 AUD inpatients. This 6-month blind phase was followed by a 12-month unblinded period in which all patients received active DBS. Continuous abstinence (primary outcome), alcohol use, alcohol craving, depressiveness, anxiety, anhedonia and quality of life served as outcome parameters. The primary intention-to-treat analysis, comparing continuous abstinence between treatment groups, did not yield statistically significant results, most likely due to the restricted number of participants. In light of the resulting limited statistical power, there is the question of whether DBS effects on secondary outcomes can nonetheless be interpreted as indicative of an therapeutic effect. Analyses of secondary outcomes provide evidence for this, demonstrating a significantly higher proportion of abstinent days, lower alcohol craving and anhedonia in the DBS-EARLY ON group 6 months after randomization. Exploratory responder analyses indicated that patients with high baseline alcohol craving, depressiveness and anhedonia responded to DBS. The results of this first randomized controlled trial are suggestive of beneficial effects of DBS in treatment-resistant AUD and encourage a replication in larger samples.